Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

The Impact of a Community Partner Research Training Program - Oluwademilade Adefarati; Rickisa Yearwood; Yawei Song; Amy E. Leader; Karen Glanz; Evelyn T. Gonzalez; Scott W. Keith; Nilsa Graciani; Thierry Fortune; Charnita M. Zeigler-Johnson (Journal of Cancer Education, 2026)
As part of its mission to address disparities in cancer outcomes and research participation, the Philadelphia Communities Conquering Cancer (PC3) coalition conducted a Community Partner Research Training program. The goal was to increase knowledge about cancer research and to prepare community members to partner on research activities. Eighteen out of 36 applicants were selected for a 5-week training program on research methods. Trainees completed baseline ( N = 18) and follow-up surveys ( N = 10) to measure knowledge acquisition. Demographic data were analyzed with descriptive statistics. For repeated cross-sectional group comparisons, Wilcoxon nonparametric tests were used to test statistical differences between medians on baseline and follow-up surveys. P -values ≤ 0.05 were considered statistically significant. Trainees were mostly female (78%). Median age was 61.5 years. Forty-four percent were Black, 22% White, 17% Asian, and 17% other race. Twenty-eight percent were Hispanic. Forty-four percent were cancer survivors. We observed that perceived knowledge about research generally increased post-training from a median of 2 to 4 across a 5-point Likert scale ( p < 0.001). This increase is shown for several items, including “how to conduct a research study” and “how to share findings with the community.” Program ratings averaged 4 out of 5, indicating positive participant experiences in program organization and content. Involving diverse populations in cancer research is crucial for reducing health disparities. This training program demonstrated that it is feasible to increase knowledge about cancer research methodology among community partners. These results will be used to guide future research activities with PC3.

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

One-step rapid synthesis Ti-O-rich Ti3C2 MXene via NH4HF2 hydrothermal etching for high charge storage - Xuefeng Sha; Xianyin Song; Qiwei Shangguan; Yawei Lv; Fan Zeng; Xingang Zhang; Xueli Wu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2026)

Rapid cultivation regulation of Methyl tert-butyl ether degradation consortium: Effects of supplemental carbon source and mechanism - Wenhao Guo; Sunyin Wang; Jun Gu; Zixi Ming; Wei Wang; Xin Song; Yawei Qian; Manjun Zhan; Ran Yu (Journal of Environmental Chemical Engineering, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Fluid-thermal-solid coupling heat transfer and flow in a co-rotating CO2 scroll compressor - Yawei Zhu; Panpan Song; Dan Dan (International Journal of Refrigeration, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

Developing a city-wide, community-engaged cancer disparities research agenda - Amy E. Leader; Yawei Song; Evelyn T. González; Thierry Fortune; Nilsa Graciani; Charnita Zeigler-Johnson; Karen Glanz (Cancer Causes & Control, 2025)
Introduction In response to high levels of cancer disparities in Philadelphia, PA, three NCI-designated clinical cancer centers formed Philadelphia Communities Conquering Cancer (PC3) to bring stakeholders together and establish infrastructure for future cancer reducing initiatives. The PC3 coalition aimed to develop a prioritized cancer disparities research agenda in order to align cancer center resources and research interests with the concerns of the community about cancer, and to ensure that initiatives were patient- and community-centered. Methods Agenda development activities culminated in a city-wide cancer disparities conference. The conference, attended by 55 diverse stakeholders, was the venue for small group discussion sessions about cancer concerns related to prevention, early detection, treatment, survivorship, and quality of life. Sessions were guided by a moderator guide and were audiorecorded, transcribed, and analyzed by the PC3 leadership team. Results were reviewed and consensus was achieved with the help of PC3’s Stakeholder Advisory Committee. Results Stakeholders identified four thematic areas as top priorities for cancer disparities research and action in Philadelphia: communication between patients, providers, and caregivers; education that reaches patients and community members with tailored and targeted information; navigation that assists people in finding and accessing the right cancer screening or treatment option for them; and representation that diversifies the workforce in clinics, cancer centers, and research offices. Conclusion A community-informed, prioritized research agenda provides a road map for the three cancer centers to collaborate on future initiatives that are important to patients and stakeholders, to ultimately reduce the burden of cancer for all Philadelphians.

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Effects of inorganic sodium on the soot generation of coal particle: Insights with PLIF and DFT calculation - Yawei Song; Sheng Su; Zheng Zhao; Jingyan Wang; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

New insights into Co3O4-carbon nanotube membrane for enhanced water purification: Regulated peroxymonosulfate activation mechanism via nanoconfinement - Huanran Ma; Guoqing Feng; Xiao Zhang; Chengwen Song; Ruisong Xu; Yawei Shi; Pengcheng Wang; Zhouhang Xu; Guanlong Wang; Xinfei Fan; Zonglin Pan (Chemosphere, 2024)

Efficient removal of organic pollutants by activation of peroxydisulfate with the magnetic CoFe2O4/carbon nanotube composite - Yawei Shi; Yi Zhang; Guobin Song; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Getting insight into the oxidation of SO2 to SO3 over P modified VW/Ti catalyst: Effect and inhibition mechanism - Zijun Yin; Yuxiu Zhong; Jingwen Lu; Tao Liu; Yawei Song; Mengxia Qing; Lele Wang; Yi Wang; Song Hu; Sheng Su; Jun Xiang (Chemical Engineering Journal, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Magnetic graphene oxide for methylene blue removal: adsorption performance and comparison of regeneration methods - Yawei Shi; Haonan Wang; Guobin Song; Yi Zhang; Liya Tong; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2022)

Sorptive removal of methylene blue from water by magnetic multi-walled carbon nanotube composites - Guobin Song; Anqi Li; Yawei Shi; Wanran Li; Haonan Wang; Chunchao Wang; Ruijuan Li; Guanghui Ding (Environmental Science and Pollution Research, 2021)

A comparison of two methods for estimating surface soil moisture based on the triangle model using optical/thermal infrared remote sensing over the source area of the Yellow River - Long Xia; Xiaoning Song; Pei Leng; Yawei Wang; Yanbin Hao; Yanfen Wang (International Journal of Remote Sensing, 2019)

Effects of Temperature and Salinity on Oxygen Consumption and Ammonium Excretion Rate of ♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus Juveniles - Daochao Xing; Xiefa Song; Lei Peng; Yawei Cheng; Jianming Zhai (Journal of Ocean University of China, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Effects of vegetation and soil texture on surface soil moisture retrieval using multi-temporal optical and thermal infrared observations - Pei Leng; Xiaoning Song; Zhao-Liang Li; Yawei Wang; Di Wang (International Journal of Remote Sensing, 2015)